Organizational Efficiency: The Role of Implementation of Total Quality Management, Work Motivation and Employee Performance - Nancy Yusnita (Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
The purpose of this study is to provide recommendations for companies to improve the performance of their employees by analyzing the relationship between the variables in this study, namely Total Quality Management (TQM), Work Motivation and Employee Performance. This research was conducted at PT. Sarandi Karya Nugraha is a health equipment fabrication company. This research is quantitative research with a survey approach. The number of samples used in the study were 112 people who were permanent employees. The method for processing and analyzing data uses Partial Least Square (PLS). The results of the study show that there is a positive and significant direct effect of the TQM on employee performance. There is a positive and significant direct effect of work motivation on employee performance. There is a positive and significant direct effect of the TQM on work motivation. There is a positive and significant indirect effect of the TQM on employee performance. through work motivation. This study shows the effective role of the intervening variable, it is work motivation.